Comparison of Zakat Management Paradigms Between Indonesia and Malaysia - Ayu Rosita Anggraini (JURNAL PENDIDIKAN IPS, 2024)
This study aims to compare the zakat management paradigms between Indonesia and Malaysia, focusing on recent developments from 2019 to 2024. Using a comparative analysis approach and systematic literature review, the study explores key aspects of zakat management in both countries, including legal and institutional frameworks, collection methods, distribution strategies. The results show significant differences in the approaches to zakat management between the two countries. Indonesia implements a centralized system under BAZNAS, while Malaysia adopts a decentralized approach at the state level. Malaysia shows higher collection efficiency through integration with the tax system, while Indonesia focuses more on voluntary compliance. Both countries show positive trends in the use of zakat for long-term development purposes, with Indonesia standing out in productive zakat initiatives and Malaysia in education and health support. The study concludes that despite differences in approach, both countries demonstrate a commitment to modernizing and optimizing their zakat management systems. Recommendations for future research include quantitative analysis of the impact of different paradigms on poverty alleviation and exploration of the potential for hybrid models that combine the strengths of centralized and decentralized systems.